Music movies for teenagers: characteristics and translation strategies - Cruz Durán, Belén (Estudios de Traducción, 2022)
Teenagers have turned into the main consumers of audiovisual productions often dubbed in their mother tongue. For that reason, the present study provides a general perspective of the characteristics of teen audiovisual productions and the translation strategies used during the 21st century, with a focus on the analysis of American teen music productions, whose music content is crucial for both the plot and characters. Teen spectators, who are going through certain stages of development and changes, need to be understood and, therefore, seek comfort in their screens. For that reason, not only the translation of dialogue exchanges, but also song translation is essential in the proper development of one of the most challenging groups of the current population.
Keywords: Teen music movies; teen movies; audiovisual translation; dubbing; subtitling; song translation